(untitled) (Research, Society and Development, 2022)
Spirulina platensis is the name associated with unicellular and filamentous blue-green microalgae, also known as cyanobacteria. Easily found in nature, records indicate that they have been found in common places such as soils, swamps, lakes and brackish waters. Biscuits stand out for their technological facilities, providing a wide variety of ingredients and formulations. An enrichment of Spirulina platensis cookies can enhance a product already on the market, thus facilitating its commercialization. This study aimed to analyze the nutritional composition of cookies enriched with Spirulina platensis through physicochemical and microbiological analyses. The research has an experimental and exploratory character, the physical-chemical characteristics were analyzed at the Water Analysis Laboratory at the Federal University Campina Grande (UFCG) on the Pombal campus, the hygienic-sanitary quality at the Food Microbiology Laboratory at UFCG. The data obtained were statistically analyzed using the Assistat 7.7 software. Based on the results, it was possible to observe that, as Spirulina was supplemented, the cookies samples changed their nutritional value in the evaluated nutrients, mainly in the protein content, as well as the preservation of the microbiological characteristics within the established standards.